2016
DOI: 10.1016/j.gaitpost.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo quantification of dynamic hip joint center errors and soft tissue artifact

Abstract: Hip joint center (HJC) measurement error can adversely affect predictions from biomechanical models. Soft tissue artifact (STA) may exacerbate HJC errors during dynamic motions. We quantified HJC error and the effect of STA in 11 young, asymptomatic adults during six activities. Subjects were imaged simultaneously with reflective skin markers (SM) and dual fluoroscopy (DF), an x-ray based technique with submillimeter accuracy that does not suffer from STA. Five HJCs were defined from locations of SM using thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 30 publications
(44 reference statements)
1
31
0
Order By: Relevance
“…These control participants had no history of hip pain. Controls were screened with an anterior‐posterior (AP) radiograph prior to study inclusion . The AP radiograph provided general screening of hip pathology, including acetabular dysplasia, Legg–Calvé–Perthes disease, and acetabular retroversion.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These control participants had no history of hip pain. Controls were screened with an anterior‐posterior (AP) radiograph prior to study inclusion . The AP radiograph provided general screening of hip pathology, including acetabular dysplasia, Legg–Calvé–Perthes disease, and acetabular retroversion.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…For each activity, two trials were captured when possible, but activity level, allotted DF time, and image quality limited the ability to capture and analyze activities from some participants (Table ). For the walking trials at a self‐selected speed, the same treadmill speed was used for level and incline walking trials based on the preferred walking speed of the participant . For all walking trails, a single gait cycle was evaluated.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to recognize that, although statistically significant, the differences may not be clinically-meaningful, as they were quite small (difference of 1.9-5.3%, calculated as 23-67 mm 2 ). We previously showed that hip translation during gait in these subjects was only 0.6 mm (Fiorentino et al, 2016a). Such small translations are unlikely to move the femoral head center enough to have a major impact on coverage, especially if the hip is spherical in shape.…”
Section: Discussionmentioning
confidence: 84%